2016
DOI: 10.5505/agri.2016.48343
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mirror Therapy on the Management of Phantom Limb Pain

Abstract: SummaryObjectives: In the last two decades, mirror therapy has become a frequently used method of managing phantom limb pain (PLP). However, the role of nurses in mirror therapy has not yet been well defined. This study examined the effect of mirror therapy on the management of PLP, and discusses the importance of mirror therapy in the nursing care of amputee patients. Methods: This quasi-experimental study was conducted in the pain management department of a university hospital and a prosthesis clinic in İsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In addition, two newer studies were not captured by the systematic reviews utilized by our review to assess the efficacy of mirror therapy and associated techniques. 130 , 131 Brunelli et al reported significant reduction in PLP intensity (n=51). However, it is impossible to identify which participants had PLP and which phantom limb sensation, as both were inclusion criteria; hence, potential bias remains high.…”
Section: Discussion – the Challenges For Future Researchmentioning
confidence: 94%
“…In addition, two newer studies were not captured by the systematic reviews utilized by our review to assess the efficacy of mirror therapy and associated techniques. 130 , 131 Brunelli et al reported significant reduction in PLP intensity (n=51). However, it is impossible to identify which participants had PLP and which phantom limb sensation, as both were inclusion criteria; hence, potential bias remains high.…”
Section: Discussion – the Challenges For Future Researchmentioning
confidence: 94%
“…Some studies combined patients with amputation of LL and UL (Darnall and Li, 2012;Sumitani et al, 2008;Yıldırım and Kanan, 2016). The first study (Darnall and Li, 2012) The greatest difference was reported by a client who had felt his phantom limb as completely stiff for 13 years, but felt strong movement illusions during MT.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15,24,28) Multiprofessional programs offering chronic pain nursing practices, with patient-centered care, low complexity psychological approaches (cognitive behavioral therapy), combined with lifestyle reorientation, are interventions that have stood out in the studies, with potential emphasis on rehabilitation, promotion of self-care, ability to promote comfort, minimization of suffering and promotion of quality of life, as well as meditation. (12,13,15,17,19,24,25) These programs constitute a multidisciplinary approach (9,16,17) and for those with pain and life-threatening risks, the implementation of a palliative care program is essential for receiving appropriate interventions from trained professionals for problematic symptoms, thus improving quality of life, as they aim to reduce pain and other symptoms. (20) The continuing offering of Continuing Education is highlighted as an important ally in pain management.…”
Section: Discussionmentioning
confidence: 99%